Sistem pendidikan nasional UU RINo.2 Th 1989 beserta peraturan pelaksanaannya 1990 - [Tidak Terdaftar] (Eko Jaya, 1990)
Sistem pendidikan nasional (UU RI No.2 Th 1989 beserta peraturan pelaksanaannya 19